2007
DOI: 10.15447/sfews.2007v5iss2art2
|View full text |Cite
|
Sign up to set email alerts
|

Processes Affecting Agricultural Drainwater Quality and Organic Carbon Loads in California's Sacramento-San Joaquin Delta

Abstract: From 2000 to 2003 we quantified drain flow, drainand ground-water chemistry and hydrogeologic conditions on Twitchell Island in the Sacramento-San Joaquin Delta. The primary objective was to quantify processes affecting organic carbon concentrations and loads in agricultural drainage water. We collected physical and chemical data in southern and northern areas: TN and TS, respectively. Corn grew in both areas during the spring and summer. The peat soils in the TN area are more decomposed than those in the TS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 27 publications
1
44
0
Order By: Relevance
“…Because DOC concentrations in shallow porewaters were so much higher than in deep pore-waters, directional flow from the shallow to deep soil layer would have resulted in pore-waters with similar DOC compositional characteristics, but this was not the case. DOC from shallow soil pore-waters of agricultural fields nearly always had lower HPoA and greater TPiA percentages, than DOC from pore-waters in deeper soils (Deverel et al 2007; Figure 6d). The similarity in DOC quality of wetland soil layers and soil layers of drained fields indicates that pre-inundation soil characteristics dominantly affect the current pore-water DOC character, despite six years of permanent flooding figure 6D, the range of DOC fractionation results from pore-waters in shallow and deep soil layers in Twitchell Island agricultural fields are provided for comparison (Deverel et al 2007).…”
Section: Ground-water Chemistrymentioning
confidence: 95%
See 3 more Smart Citations
“…Because DOC concentrations in shallow porewaters were so much higher than in deep pore-waters, directional flow from the shallow to deep soil layer would have resulted in pore-waters with similar DOC compositional characteristics, but this was not the case. DOC from shallow soil pore-waters of agricultural fields nearly always had lower HPoA and greater TPiA percentages, than DOC from pore-waters in deeper soils (Deverel et al 2007; Figure 6d). The similarity in DOC quality of wetland soil layers and soil layers of drained fields indicates that pre-inundation soil characteristics dominantly affect the current pore-water DOC character, despite six years of permanent flooding figure 6D, the range of DOC fractionation results from pore-waters in shallow and deep soil layers in Twitchell Island agricultural fields are provided for comparison (Deverel et al 2007).…”
Section: Ground-water Chemistrymentioning
confidence: 95%
“…Groundwater flow directions are primarily lateral from the pond to the adjacent drainage ditch, and upward from the sand and silt layers into the organic soils. The broader hydrogeologic framework for the study area is described in greater detail in Burow et al (2005), Gamble et al (2003), and Deverel et al (2007 …”
Section: Site Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher percentages are associated with winter drainage. Deverel et al (2007) demonstrated that oxidation of soil organic matter and subsequent mobilization of DOC to drainage ditches are the primary mechanisms that lead to DOC export from subsided Delta islands. Oxidation of soil organic matter in drained agriculture also results in losses of carbon dioxide that range from 15 to 20 tons carbon dioxide per ha (e.g., Knox et al 2015), which could be stopped or greatly reduced if islands are converted to rice and permanently-flooded carbon sequestration wetlands (Knox et al 2015) or tidal wetlands.…”
Section: Maintaining the Status Quomentioning
confidence: 99%